2014
DOI: 10.1037/a0035441
|View full text |Cite
|
Sign up to set email alerts
|

From sound to shape: Auditory perception of drawing movements.

Abstract: This study investigates the human ability to perceive biological movements through friction sounds produced by drawings and, furthermore, the ability to recover drawn shapes from the friction sounds generated. In a first experiment, friction sounds, real-time synthesized and modulated by the velocity profile of the drawing gesture, revealed that subjects associated a biological movement to those sounds whose timbre variations were generated by velocity profiles following the 1/3 power law. This finding demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 62 publications
2
65
0
Order By: Relevance
“…As highlighted in previous studies, it is through the structural and transformational invariants present in the sound (Thoret, Aramaki, Kronland-Martinet, Velay, & Ystad, 2014), that participants can anticipate the attacker's movement kinematics (e.g. velocity, trajectory, position).…”
Section: Action Anticipation Through Its Sound Alone 21 21mentioning
confidence: 91%
“…As highlighted in previous studies, it is through the structural and transformational invariants present in the sound (Thoret, Aramaki, Kronland-Martinet, Velay, & Ystad, 2014), that participants can anticipate the attacker's movement kinematics (e.g. velocity, trajectory, position).…”
Section: Action Anticipation Through Its Sound Alone 21 21mentioning
confidence: 91%
“…This step was recently performed by Thoret, Aramaki, Kronland-Martinet, Velay, and Ystad (2014) who demonstrated that adult subjects were able to infer by ear what was drawn based, only, on the generated friction sounds. Their rationale was that, although handwriting is not really a noisy activity, the slight sounds generated by the pen friction on the paper can be heard in a silent environment.…”
Section: Introductionmentioning
confidence: 98%
“…For example, some studies have shown providing sound synthesis can improve hands gesture accuracy on mobile devices [4], communication with geometrical data on screen [1], and impressions during the writing task [3]. Futhermore, some recent studies suggest audio feedback is effective for the drawing shape recognition [2,5]. We aim to apply visual and auditory effects for improvement of drawing skill.…”
Section: Related Workmentioning
confidence: 96%
“…One is to apply an existed friction model with changing sound according to velocity and pressure of pen tip. This is because Thoret et al [5] suggest the possibility of the relation between drawn shapes and friction sounds, which strongly suggests that common rules constrain perception and action of biological motions. The other one is to synthesize sound with changing the audio parameters according to the drawing motion (e.g., x axis: panning, y axis: frequency, pressure: volume) and to provide a metronome sound.…”
Section: Design Of Visual and Auditory Feedbackmentioning
confidence: 97%